2019
DOI: 10.12688/f1000research.16561.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the basis of sexual dysfunction during late-onset hypogonadism

Abstract: Late-onset hypogonadism (LOH) is the term used to describe the decline in serum testosterone levels associated with increasing age in men above 40 years. A number of symptoms are attributed to LOH, but the most common association is that of sexual dysfunction. LOH has recently come under greater scrutiny with the widespread use of testosterone therapy, and concerns regarding the efficacy and safety of testosterone replacement therapy have been raised. In particular, the cardiovascular safety and the beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…14 FH has recently come under greater scrutiny with the widespread use of testosterone therapy (TTh), and concerns regarding the efficacy and safety of TTh have been raised. 15 TTh may exert several benefits with regard to metabolic profile, body composition, psychological, and sexual parameters. Multiple studies have shown that TTh applied to obese men with FH and T2D improves glycemic control; reduces insulin resistance (IR), inflammation, and symptoms of hypogonadism; increases bone mineral density; and improves vascular function and morphology along with improvements in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…14 FH has recently come under greater scrutiny with the widespread use of testosterone therapy (TTh), and concerns regarding the efficacy and safety of TTh have been raised. 15 TTh may exert several benefits with regard to metabolic profile, body composition, psychological, and sexual parameters. Multiple studies have shown that TTh applied to obese men with FH and T2D improves glycemic control; reduces insulin resistance (IR), inflammation, and symptoms of hypogonadism; increases bone mineral density; and improves vascular function and morphology along with improvements in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“… 59 Also, they lack specificity for HG and therefore, should be utilized after the diagnosis of HG through measurement of testosterone has been established. 8 In that regard, if symptoms persist during follow-up other pathologies must be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Sexuality is an important aspect of human life, and emotions related to sexual activity influence mental well-being, relationship, or how we see ourselves. Sexual function disorders (e.g., erectile dysfunction) caused by prostate carcinoma significantly reduces the quality of life of men [6][7][8]. Cancer treatment is also related to reduced sex drive and penile dysfunction manifesting itself through, for example, reduced ability to have an orgasm, erectile disorders, or urinary incontinence [9,10].…”
Section: Discussionmentioning
confidence: 99%